The Oxford handbook of the history of linguistics - Allan, Keith, 1943- (Oxford : Oxford University Press, 2013)
In this outstanding book leading scholars from around the world examine the history of linguistics from ancient origins to the present. They consider every aspect of the field from language origins to neurolinguistics, explore linguistic traditions in east and west, chronicle centuries of explanations for language structures, meanings, and usage, and look at how it has been practically applied. This handbook makes a significant contribution to the historiography of linguistics. It will also be a valuable reference for scholars and students in linguists and related fields, including philosophy and cognitive science.
Includes bibliographical references and index.
Keywords: Linguistics -- History; Australian